Recent Advances in Mainstream Hemostasis Diagnostics and Coagulation Testing - Favaloro, Emmanuel J.; Lippi, Giuseppe (Seminars in Thrombosis and Hemostasis, 2019)
The authors provide a narrative review of mainstream hemostasis analyzers. The review is presented in two parts. In the first part, the authors give voice to several internationally representative manufacturers of mainstream hemostasis analyzers. They ask these manufacturers to (1) answer a series of survey questions that may otherwise reflect common questions asked by users or potential users of their equipment, (2) provide a bullet list of their main focus areas, and (3) provide other information in regard to their instrumentation. The authors then offer their own personal perspective of the benefits of various aspects of such equipment, as well as a sampling of some hemostasis tests as currently available, or potentially in progress. It is hoped that this snapshot of mainstream hemostasis diagnostics and coagulation testing drives positive future changes that will ultimately provide the best outcomes for laboratories performing hemostasis assays and the patients they help diagnose and manage.
Keywords: hemostasis; analyzer; instrumentation; equipment; coagulation; testing